Edwin 'Ted' Milliken interviewed by Glenys Dimond in the Bringing them home oral history project - Milliken, E. P. (Edwin Percival), 1918-; Dimond, Glenys, 1950- (2001)
Milliken speaks about his childhood in Queensland and his early working life. He served in the Navy from 1942 to 1947 and was part of the psychology unit. After leaving the Navy, Milliken took a position as a psychologist with the Department of Labour and National Service and then in 1953 he transferred to the Northern Territory as Research Director, Welfare Division. He talks about the Aboriginals Ordinance and the Child Welfare Ordinance, and the role of the Welfare Division in child removals. In 1973, Milliken became a senior lecturer at the Darwin Community College. He expresses his opinion on the Bringing Them Home report.
Recorded on Oct. 3, 2001 in Parap, Darwin, N.T.
Digital master available
Timed summary (6 p.) and uncorrected transcript (typescript, 40 leaves)
Keywords: Milliken, E. P. -- 1918- -- Interviews; Northern Territory Administration. -- Welfare Division -- Periodicals; Psychologists -- Australia -- Interviews; Aboriginal Australians -- Government policy -- Northern Territory; Aboriginal Australians -- Northern Territory -- Removal; Aboriginal Australians -- Northern Territory -- Child welfare; Child welfare -- Northern Territory -- Administration; Aboriginal Australians -- Northern Territory -- Legal status, laws, etc